Xenon Reduces Neuronal Hippocampal Damage and Alters the Pattern of Microglial Activation after Experimental Subarachnoid Hemorrhage: A Randomized Controlled Animal Trial - Veldeman, Michael; Coburn, Mark; Rossaint, Rolf; Clusmann, Hans; Nolte, Kay; Kremer, Benedikt; Höllig, Anke (Frontiers in Neurology, 2017)
Objective The neuroprotective properties of the noble gas xenon have already been demonstrated using a variety of injury models. Here, we examine for the first time xenon’s possible effect in attenuating early brain injury (EBI) and its influence on posthemorrhagic microglial neuroinflammation in an in vivo rat model of subarachnoid hemorrhage (SAH). Methods Sprague-Dawley rats (n = 22) were randomly assigned to receive either Sham surgery (n = 9; divided into two groups) or SAH induction via endovascular perforation (n = 13, divided into two groups). Of those randomized for SAH, 7 animals were postoperatively ventilated with 50 vol% oxygen/50 vol% xenon for 1 h and 6 received 50 vol% oxygen/50 vol% nitrogen (control). The animals were sacrificed 24 h after SAH. Of each animal, a cerebral coronal section (−3.60 mm from bregma) was selected for assessment of histological damage 24 h after SAH. A 5-point neurohistopathological severity score was applied to assess neuronal cell damage in H&E and NeuN stained sections in a total of four predefined anatomical regions of interest. Microglial activation was evaluated by a software-assisted cell count of Iba-1 stained slices in three cortical regions of interest. Results A diffuse cellular damage was apparent in all regions of the ipsilateral hippocampus 24 h after SAH. Xenon-treated animals presented with a milder damage after SAH. This effect was found to be particularly pronounced in the medial regions of the hippocampus, CA3 (p = 0.040), and dentate gyrus (DG p = 0.040). However, for the CA1 and CA2 regions, there were no statistical differences in neuronal damage according to our histological scoring. A cell count of activated microglia was lower in the cortex of xenon-treated animals. This difference was especially apparent in the left piriform cortex (p = 0.017). Conclusion In animals treated with 50 vol% xenon (for 1 h) after SAH, a less pronounced neuronal damage was observed for the ipsilateral hippocampal regions CA3 and DG, when compared to the control group. In xenon-treated animals, a lower microglial cell count was observed suggesting an immunomodulatory effect generated by xenon. As for now, these results cannot be generalized as only some hippocampal regions are affected. Future studies should assess the time and localization dependency of xenon’s beneficial properties after SAH.